From friends to foes: National identity and collaboration in diverse teams - Nadzeya Laurentsyeva (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
This project studies collaboration in highly skilled, nationally diverse teams. An unexpected international political conflict makes national diversity more salient among existing and potential team members. I exploit this natural experiment to quantify the role of social, identity-driven, costs for performance and formation of diverse teams. Using microdata from GitHub, the world's largest hosting platform for software projects, I estimate the causal impacts of a political conflict that burst out between Russia and Ukraine in 2014. I find that the conflict strongly reduced online cooperation between Russian and Ukrainian programmers. The conflict lowered the likelihood that Ukrainian and Russian programmers work in the same team and led to the performance decline of existing joint projects. I provide evidence that the observed effects were not driven by economic considerations. Rather, the conflict activated national identities and shifted programmers' taste for teammates and projects. My results highlight the role of identity-driven concerns that can distort existing and prevent future collaborations, otherwise profitable from an economic perspective.
Keywords: D22; D74; F23; F51; J71; 330; Teams; Diversity; Conflict; National identity; Open source